Analisis Kesadaran Hukum Berlalu Lintas Siswa ditinjau dari Perspektif Civic Competence Siswa di SMA Negeri 3 Bungo - Fitriani, Aida Nur; Candra, Alif Aditya; Sariani, Dona (AHKAM, 2025)
Legal awareness in traffic reflects the extent to which individuals understand, accept, and comply with legal regulations in daily life. Among students, deviant behavior still occurs, indicating the need to strengthen legal understanding. This study aims to analyze students' traffic law awareness from the perspective of civic competence at SMA Negeri 3 Bungo, which includes the dimensions of civic knowledge, civic skills, and civic disposition. The study uses a descriptive qualitative approach with purposive sampling in selecting informants, consisting of seven Grade X and XI students as primary informants, one Pancasila Education teacher as a key informant, and one vice principal for curriculum as an additional informant. Data were collected through interviews, observations, and documentation, and analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that students’ civic knowledge is relatively good in understanding basic rules, but they lack deep comprehension of formal legal provisions such as traffic laws. In terms of civic skills, students actively participate in awareness activities but remain passive in responding to violations in their surroundings. Meanwhile, their civic disposition still relies on external supervision and has not developed into intrinsic awareness. In conclusion, students' underdeveloped civic competence contributes to their low traffic law awareness. The theoretical implication reinforces the concept that legal awareness is not solely dependent on knowledge but also on citizenship skills and attitudes. The practical implication encourages schools to strengthen the comprehensive teaching of Pancasila Education to foster more effective and sustainable legal awareness. Keywords: civic competence; legal awareness; traffic; students; Pancasila Education